Large-Scale Social Collaboration Policy in the Food Sector in DKI Jakarta: A Socio-Cultural Perspective - Marullah Matali; Wirman Syafri; Ermaya Suradinata; Mansyur Achmad (Buletin Al-Turas, 2023)
PurposeThis research aims to reveal the implementation of Large-Scale Social Collaboration (LSSC) policy in the food sector in DKI Jakarta, especially during the Covid-19 pandemic seen from the socio-cultural perspective to produce a solution policy model. MethodsThe study employed a qualitative approach with a descriptive research design as it tried to elaborate how the society perceived LSCC policy during the Covid-19 pandemic. The data of this research is the LSSC policy issued by DKI Jakarta Provincial Government, and the society's perception and opinions sourced from aggregators, collaborators, and beneficiary communities. The data was got by conducting a review on LSSC policy, interview, and observation of the policy implementation process.  FindingsThe study reveals the government of DKI Jakarta has implemented LSSC policy in the food sector during the Covid-19 pandemic well. However, there were several shortcomings must be improved, including data synchronization, socialization, and limited regulations by introducing two policy models, namely IEFFB and MATALI. IEFFB stands for improving DKI Jakarta's food security, ensuring people's food needs, fostering a sense of togetherness and care, forming a collaborative system between the government, private sector and the community to overcome common problems, and becoming a policy role model for other regions. MATALI that stands for motivation, actualization, trust, ability, leadership; and innovation is six important aspects of implementing the LSSC food sector policy. ConclusionThe study concludes that implementing LSSC policy in the food sector in DKI Jakarta still needs a serious improvement as a new policy solution for LSSC after Covid-19 pandemic.